Excess capacity and pricing in Bertrand-Edgeworth markets: Experimental evidence - Miguel A. Fonseca; Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We conduct experiments testing the relationship between excess capacity and pricing in repeated Bertrand-Edgeworth duopolies and triopolies. We systematically vary the experimental markets between low excess capacity (suggesting monopoly) and no capacity constraints (suggesting perfect competition). Controlling for the number of firms, higher production capacity leads to lower prices. However, the decline in prices as industry capacity rises is less pronounced than predicted by Nash equilibrium, and a model of myopic price adjustments has greater predictive power. With higher capacities, Edgeworth-cycle behavior becomes less pronounced, causing lower prices. Evidence for tacit collusion is limited and restricted to low-capacity duopolies.
Keywords: C72; C90; D43; 330; tacit collusion; excess capacity; Edgeworth cycles